Synthesis of OSL nanophosphor Li3B7O12:Mn and its dosimetric properties. (10th October 2018) - Agarwal, Mini; Asokan, K; Garg, S K; Dhamija, E; Kumar, Pratik
Abstract: The present paper reports the structural, morphological and optical properties of nanophosphor Li3 B7 O12 :Mn with an optimised dopant concentration of 0.25 mol% and its surface modification under the irradiation of 250 keV proton beams and gamma photons for ion fluence ranging from 1 × 10 13 to 6.25 × 10 15 ions cm −2 and doses from 100 mGy–100 Gy, respectively. This nanophosphor has been synthesised by the high temperature solid state reaction method. Its optical properties are characterised by optically stimulated luminescence (OSL) and thermo luminescence (TL) techniques. This nanophosphor is polycrystalline in nature with a grain size of 40–80 nm confirmed by x-ray diffraction (XRD) and transmission electron microscopy (TEM). The OSL decay and TL glow curve response of the proton beam irradiated samples exhibit significant intensity at a fluence of 2.5 × 10 14 ions cm −2 . Moreover, Li3 B7 O12 :Mn displays a linear response for gamma doses in the range of 100 mGy–50 Gy. We have also investigated the reusability and reproducibility of this material. The above study demonstrates that Li3 B7 O12 :Mn is a robust and promising candidate for medical proton dosimetry.